2011
DOI: 10.1038/npp.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

A Novel α5GABAAR-Positive Allosteric Modulator Reverses Hyperactivation of the Dopamine System in the MAM Model of Schizophrenia

Abstract: We have shown previously that aberrant hippocampal (HPC) output underlies the dopamine (DA) dysfunction observed in the methylazoxymethanol acetate (MAM) developmental model of schizophrenia in the rodent. This alteration of HPC activity was proposed to result from a reduction in parvalbumin (PV)-expressing GABAergic interneurons and consequent destabilization of the output of pyramidal neurons, as well as disrupted activation across a broad neural network. In vivo extracellular recordings were performed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
189
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(221 citation statements)
references
References 55 publications
28
189
3
1
Order By: Relevance
“…In the MAM rodent model of schizophrenia, augmented dopamine system function (measured by directly recording spontaneous dopamine neuron activity in the VTA) and aberrant behaviors, such as the hyper-responsivity to psychomotor stimulants and deficits in cognitive flexibility, are mediated by increased hippocampal activity (Gill et al, 2011;Lodge and Grace, 2007;Perez et al, 2013). Similarly, schizophrenia patients exhibit enhanced baseline hippocampal activity that is correlated with the severity of positive symptoms (Schobel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the MAM rodent model of schizophrenia, augmented dopamine system function (measured by directly recording spontaneous dopamine neuron activity in the VTA) and aberrant behaviors, such as the hyper-responsivity to psychomotor stimulants and deficits in cognitive flexibility, are mediated by increased hippocampal activity (Gill et al, 2011;Lodge and Grace, 2007;Perez et al, 2013). Similarly, schizophrenia patients exhibit enhanced baseline hippocampal activity that is correlated with the severity of positive symptoms (Schobel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These fast firing interneurons are known to maintain the oscillatory activity of excitatory glutamatergic pyramidal neurons through perisomatic targeting (Lewis et al, 2005;Lodge et al, 2009). Moreover, studies have further shown that attenuation of hyperactivity of neurons in the ventral hippocampus via drug treatment or deep brain stimulation can normalize the enhanced dopamine neuron activity, thereby reversing an augmented locomotor response to amphetamine seen in animal models of schizophrenia (Gill et al, 2011;. Thus, the concept of GABAergic interneuron transplantation into the hippocampus as a therapy for schizophrenia stems from the observation that persistent hippocampus hyperactivity promotes dopamine hyperfunction and that addition of new GABA-ergic interneurons into the hippocampus circuitry would restrain this hyperactivity.…”
Section: Gaba-ergic Cell Grafts For Treating Schizophreniamentioning
confidence: 99%
“…The DNA-methylating agent, methylaxozymethanol acetate (MAM), induces a developmental model of schizophrenia whereby affected animals exhibit both the structural and behavioral abnormalities that are normally seen in schizophrenia [31]. These animals were found to exhibit an increase in dopaminergic activity within the ventral tegmental area (VTA) that was thought to be due to hippocampal hyperactivity [32].…”
Section: Current Drug Targets 2015mentioning
confidence: 99%
“…This was investigated by monitoring of VTA neurons in MAM rats in the presence of SH-053-2'F-R-CH3 ( Table 1, 2), a benzodiazepine α 5 -selective positive modulator [31]. This compound successfully diminished the number of spontaneously active dopaminergic neurons in the VTA in addition to reversing the heightened locomotor response to low dose of D-amphetamine in MAM but not in control rats [31], supporting the possible use of a similar treatment in schizophrenia. Given that inhibition of α 5 GABA A Rs enhances learning and memory [14,34], it is feasible that an enhancer like SH-053-2'F-R-CH3 could produce anterograde memory impairment; however, no such memory impairment has been observed [35].…”
Section: Current Drug Targets 2015mentioning
confidence: 99%
See 1 more Smart Citation